PENGARUH MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) BERBANTUAN VIDEO ANIMASI TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA MATERI SISTEM PENCERNAAN MANUSIA - Rohaeni, Rian; Cecep Sodikin; Poppy Anggraeni (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research is motivated by the low critical thinking skills of students. One way that is expected to improve students' critical thinking skills is to use the RADEC learning model assisted by animated videos. The purpose of this study was to determine the size of the influence of the RADEC learning model assisted by animated videos on students' critical thinking skills on the human digestive system material in class V SDN Cijambu II.The research method used is a pre-experimental method with a quantitative approach. The research design used is one-group pretest posttest. The data collection technique in this study was a test technique consisting of a pretest (pretest) and a final test (posttest). The sample in this study were all students of class V SDN Cijambu II, totaling 30 students.Based on the results of the t-test calculation, the tcount value is 16.66 > ttable 1.699, so H1 is accepted and Ho is rejected. Based on the results of the n-gain calculation, an average of 0.51 was obtained in the medium category and based on the results of the effect size calculation, a value of 1.67 was obtained with the large category. Thus, it can be concluded that the RADEC learning model assisted by animated videos has a major effect on students' critical thinking skills on the material of the human digestive system in class V SDN Cijambu II, Tanjungsari sub-district, Sumedang district in the 2021/2022 school year